Refuge in law as an answer to negative realities according to justice. The progress towards the inadmissibility of death penalty - Antonio Iaccarino (Vergentis. Revista de Investigación de la Cátedra Internacional Conjunta Inocencio III, 2020)
The text addresses the peculiar bond that link together the philosophy of law and the history of law and it proposes again the current need to “rethink the thought” on law, so that it can be the dialogic tool to structure a vision of the world able to generate awareness, responsible action, that creates and performs reality. The text analyses the topic of the positive utopia of reality, in connection with the principle of fraternity, and a way to think about the relation of otherness as “thinking in reciprocity” is defined. Lastly, as practical field of this proposal, it is proposed the overcoming of the death penalty, in the light of the theory of restorative justice.